2021
DOI: 10.1007/s11596-021-2313-6
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Treatment of Patients with Coronavirus Disease 2019: A Propensity Score Matching Study

Abstract: The role of corticosteroids in the treatment of coronavirus disease 2019 (COVID-19) is controversial. In the present study, we evaluated the effects of adjuvant corticosteroids treatment on the outcome of patients with COVID-19 (n=966), using Propensity Score Matching to adjust for potential differences between the corticosteroids group (n=289) and the non-corticosteroids group (n=677). Analysis of data without adjusting differences in baseline characteristics indicated that the proportion of mechanical ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These studies included 2,214 laboratory-confirmed COVID-19 patients not requiring supplemental oxygen, 833 receiving systemic corticosteroid treatment, and 1,381 without. Although 6 of the 7 studies examined methylprednisolone, 6 , 7 , 8 , 9 , 10 , 11 the study that contributed the most patients to the meta-analysis used a 6 mg/day dose of oral or intravenous dexamethasone for 10 days. 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included 2,214 laboratory-confirmed COVID-19 patients not requiring supplemental oxygen, 833 receiving systemic corticosteroid treatment, and 1,381 without. Although 6 of the 7 studies examined methylprednisolone, 6 , 7 , 8 , 9 , 10 , 11 the study that contributed the most patients to the meta-analysis used a 6 mg/day dose of oral or intravenous dexamethasone for 10 days. 12 …”
Section: Resultsmentioning
confidence: 99%
“…20 , 21 Also, only 3 studies explicitly excluded patients on chronic systemic corticosteroids. 6 , 8 , 9 Chronic systemic corticosteroid use is a risk factor for severe COVID-19 infection in, for example, asthma and chronic liver disease patients 22 , 23 ; therefore, possible selection of these high-risk patients into the corticosteroid groups in the propensity score matching studies could have biased the results against corticosteroids. Lastly, the authors excluded studies from their analysis in which no patients died or progressed to severe disease in either treatment group.…”
Section: Commentarymentioning
confidence: 99%
“…[ 24 ] Glucocorticoids were widely concerned due to the beneficial effects in overcoming both hyperinflammation and ARDS. [ 25 , 26 ] Previous studies revealed that the use of glucocorticoids could decrease the mortality of COVID-19 patients, [ 11 13 ] but the results were inconsistent. [ 19 , 20 ] To assess the therapeutic effect of glucocorticoids in severe COVID-19 patients, we analyzed the data of 6612 severe COVID-19 patients from 13 studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of three meta-analysis further support the employ of systemic corticosteroids in COVID-19 pneumonia, but it is worth to mention that the weight of RECOVERY trial was more than 50 per cent in all of them and the magnitude of the effect was modest (OR ranging from 0.70 to 0.88) [ 41 43 ]. On the other hand, several propensity score matching (PSM) studies found no impact of corticosteroids on COVID-19 pneumonia outcome [ 44 49 ], while an increased mortality was observed in other report [ 50 ] and two additional PSM studies concluded that corticosteroid therapy was associated with lower mortality [ 51 , 52 ]. Therefore, considering all the available evidence, the role of corticosteroids remains controversial in non-critically ill patients who need supplemental oxygen.…”
Section: Discussionmentioning
confidence: 99%